Jozimine A2, a dimeric naphthylisoquinoline (NIQ) alkaloid, shows in vitro cytotoxic effects against Leukemia cells through NF-κB inhibition - Damiescu, Roxana; Yücer, Rümeysa; Klauck, Sabine; Bringmann, Gerhard; Efferth, Thomas; Dawood, Mona (International journal of molecular sciences, 2024)
Naphthylisoquinoline (NIQ) alkaloids are rising as a promising class of secondary metabolites with pharmaceutical potential. NF-κB has already been recognized as a significant modulator of cancer proliferation and drug resistance. We have previously reported the mechanisms behind the cytotoxic effect of dioncophylline A, an NIQ monomer, in leukemia cells. In the current study, we have investigated the cytotoxic effect of jozimine A2, an NIQ dimer, on leukemia cells in comparison to a second, structurally unsymmetric dimer, michellamine B. To this end, molecular docking was applied to predict the binding affinity of the dimers towards NF-κB, which was then validated through microscale thermophoresis. Next, cytotoxicity assays were performed on CCRF-CEM cells and multidrug-resistant CEM/ADR5000 cells following treatment. Transcriptome analysis uncovered the molecular networks affected by jozimine A2 and identified the cell cycle as one of the major affected processes. Cell death modes were evaluated through flow cytometry, while angiogenesis was measured with the endothelial cell tube formation assay on human umbilical vein endothelial cells (HUVECs). The results indicated that jozimine A2 bound to NF-κB, inhibited its activity and prevented its translocation to the nucleus. In addition, jozimine A2 induced cell death through apoptosis and prevented angiogenesis. Our study describes the cytotoxic effect of jozimine A2 on leukemia cells and explains the interactions with the NF-κB signaling pathway and the anticancer activity.
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 16.08.2024